Detectability of Chiari Malformation and Other Craniovertebral Junction Anomalies Using Computed Tomography - M. N. Mikhailova; O Yu. Kostrova; P. A. Svyatochevskiy; L. M. Merkulova; G. Yu. Struchko; Yu. I. Pavlov; A. Yu. Semenov (Вестник рентгенологии и радиологии)
Background. Due to development of new diagnostic technologies, craniovertebral junction anomalies have begun to be detected more frequently. The most clinically significant is the Chiari malformation (CM), or Arnold–Chiari anomaly.Objective: to analyze the incidence of various types of CM, Kimmerle anomaly (KA) and other craniovertebral anomalies, assess its dependence on craniometric parameters according to the protocols of radiological studies and neurosurgical department data for 5 years.Material and methods. The results of computed tomography (CT) and Doppler ultrasound performed in patients of the Republican Clinical Hospital (Chuvash Republic) in 2017–2021 were studied. Craniometry was carried out using CT data, and the incidence of craniovertebral anomalies was assessed depending on skull shape. Discharge reports of patients from the neurosurgical department were analyzed for the same period.Results. According to CT results, detection rate for CM causing hospitalization in the neurosurgical department was 7.6–7.8 cases per year. CM was 1.5–3 times more common in female patients, but in males it manifested at a younger age. The likelihood of this pathology was highest in persons with brachycephalic scull. CM was combined with other anomalies of skull and spine bone structure (platybasia, basilar impression, spina bifida posterior) in 18.4% of observations, and with KA in 31% of cases. Surgical decompression of craniovertebral junction was required in 77% of patients, 2/3 of which had signs of syringomyelia.Conclusion. CM is more often found in female patients, however, its clinical manifestations, which cause hospitalization in neurosurgical department, occur in males at a younger, most able-bodied age. The likelihood of detecting this anomaly is higher in patients with brachycrania. In almost half of CM patients, it may be combined with other craniovertebral junction anomalies, most commonly with KA.